Blockchain untuk Penggalangan Dana Filantropi di Indonesia: Meningkatkan Transparansi, Akuntabilitas, dan Kepercayaan Publik - Muhammad Rizky; Teduh Dirgahayu (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
Indonesia’s philanthropic sector faces significant challenges related to transparency and accountability, which undermine public trust, especially in donation management through crowdfunding platforms. This paper aims to explore the potential of blockchain technology for enhancing transparency and accountability in philanthropic crowdfunding by adapting the Blockchain-Based Donation Traceability (BBDT) framework. Using the Design Science Research methodology, data were collected through interviews with two major philanthropic organisations (Baitul Maal Hidayatullah and Human Initiative) and a survey involving 180 respondents. Survey results showed that 72% of respondents consider donation tracking very important, and 81.9% believe that blockchain could enhance transparency. A prototype of a blockchain-based donation system for philanthropic organisations was designed and developed, featuring functionalities to meet user needs identified during interviews. The prototype was demonstrated to Baitul Maal Hidayatullah and Human Initiative, with all transactions executed on the Ethereum testnet and the local Ganache network. The demonstration showed that blockchain implementation can enhance transparency and accountability through real-time donation tracking and automated reporting. However, barriers to adoption, such as limited public familiarity with cryptocurrency and digital wallets, remain substantial, indicating that transactions should still be conducted in rupiah, with blockchain used solely for transparent transaction recording. In conclusion, blockchain demonstrates strong potential to support digital philanthropy, while ongoing education and system adaptation are essential.